Réponses

2013-04-03T15:13:10+02:00

Bonjour.

 

On a :

 

x + y = 13

x² - y² = 39

 

donc:

 

x + y = 13

(x+y) * (x-y) = 39 -> 13 (x-y) = 39 -> x-y=3

 

donc

 

x + y = 13

x - y = 3

 

->

 

x + y + x - y = 16

-> 2x = 16

 

x = 8

 

puis y =5

2013-04-03T15:14:22+02:00

Bonjour,

 

C'est très simple,

Utilise la méthode de la substitution.

 

x+y=13

x² -y² =39

 

y = 13 - x

x² - (13 - x)² = 39

 

y = 13 - x

x² - (169 - 26x + x²) = 39

 

y = 13 - x

x² - 169 + 26x - x² = 39

 

y = 13 - x

26x = -130

 

y = 13 - x

x = -5

 

y = 18

x = -5

 

En espérant avoir pu t'aider :D